Prevalence of ritual images in yoruba nollywood films and the perception of contemporary society (2017)
Studies have shown that a majority of Nollywood movies are a reflection of the Nigerian people’s traditional and cultural performances. This study posits that these themes are always explored to reinforce the existing cultural values and beliefs in the society. It is against this backdrop that this study examined the influence of ritual images in three selected Yoruba Nollywood films; Okanran (2014), Alani Pamolekun (2015) and Ija Yemoja (2016) on the viewers and the applicability to solve real life problems. Employing the content analysis and survey technique, evidence shows that the audience are exposed to the prevalence of ritual images such as charms, sacrifice, incantation, spell, concoction, wands, totems, shrines and other ritual performances in Yoruba films. The sampled audience observed that the projection of ritualism in Yoruba Nollywood movies is overemphasized as the reality of such practice is not so common in real life situations. Hence, there is a need for film producers to censor the overemphasis of certain cultural themes as these may somewhat be at the detriment of film audience and their perception of reality.